Decolourisation of textile dye by laccase: Process evaluation and assessment of its degradation bioproducts. (November 2021) - Yadav, Ashutosh; Yadav, Pooja; Kumar Singh, Anil; kumar, Vyas; Chintaman Sonawane, Vijay; Markandeya; Naresh Bharagava, Ram; Raj, Abhay
Graphical abstract: Highlights: Rapid Remazol Brilliant Blue R dye decolourisation achieved by laccase without redox mediator. Optimization by Box–Behnken design enhanced dye decolourisation (97.18%). Dye degradation has been affirmed by UV–visible spectroscopy and FTIR analysis. Laccase treated dye found relatively less phyto- and cytotoxic. Molecular docking analysis revealed the significant binding affinity between RBBR-laccase. Abstract: Biodegradation of environmentally hazardous synthetic dyes by enzymes has been achieved the highest interest in recent years. In this work, we optimized Remazol Brilliant Blue R (RBBR) dye biodegradation by Arthrographis kalrae derived laccase via the Box-Behnken design (BBD) approach of the surface response methodology (RSM). Optimization of dye decolourisation by one variable at a time (OVAT) approach resulted in optimal dye decolourisation at laccase dose (2 IU mL −1 ), pH (7.0), temperature (35 °C), incubation time (240 min), and initial dye concentration (100 mg L -1 ). The optimized process through BBD enhanced dye decolourisation (97.18%). Fourier Transform Infrared Spectroscopy and UV–Visible Spectrophotometry have proven biodegradation. In addition, in comparison to untreated samples, the laccase-treated dye sample showed relatively less phyto- and cytotoxic effect on Allium cepa L. Extra Precision Glide docking exhibited the binding affinity score of −5.355 kcal mol −1, between laccase-RBBR complex.